2009
DOI: 10.1159/000219331
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Gastric Cancer No Longer Presents as an Advanced Disease with Ominous Prognosis

Abstract: Background: This study aimed to characterize the clinicopathological features and prognosis of early onset gastric carcinomas (EOGCs) in a sample of young Portuguese adults. Material and Methods: A subset of 415 patients submitted to gastric resection was divided into 2 groups: A – patients aged 45 years or less (n = 108), and B – patients older than 45 years (n = 307). The groups were compared for several clinicopathological features and the survival of the patients was analyzed by uni- and multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Other studies have suggested that advanced disease stage and the presence of distant metastasis produce worse surgical outcomes 10. Furthermore, Moreira et al 20 found that tumor location, Carneiro's histological classification, depth of tumor invasion, lymphatic invasion, nodal involvement, vascular invasion, distant metastases, and stage in univariate analysis have significant impacts on survival. In the present study, advanced nodal involvement, deeper tumor invasion, bigger tumor size, and positive resection margins were independent factors for young patients with poorer survival by multivariate analysis (Table III, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have suggested that advanced disease stage and the presence of distant metastasis produce worse surgical outcomes 10. Furthermore, Moreira et al 20 found that tumor location, Carneiro's histological classification, depth of tumor invasion, lymphatic invasion, nodal involvement, vascular invasion, distant metastases, and stage in univariate analysis have significant impacts on survival. In the present study, advanced nodal involvement, deeper tumor invasion, bigger tumor size, and positive resection margins were independent factors for young patients with poorer survival by multivariate analysis (Table III, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the prognosis of GC patients undergoing resection is influenced by age remains controversial 7, 9, 10, 20. Studies have shown that young patients have worse survival than old patients, but more advanced diseases have been noted in the young 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few subsequent studies reported that the prognosis and survival rate were not significantly different between young and older patients after matching for tumor stage. 3,13,18 Furthermore, the prognosis and survival rate of young patients after curative resection were better than those of older patients. [5][6][7]9,13 Owing to awareness about aggressive tumor biology and rapid progression in young patients with gastric cancer, there were concerns about endoscopic local treatment in young patients with EGC, even for those that met the expanded indication for ESD.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the importance of developing a thorough investigation of at-risk individuals and young patients who present with gastric symptoms, as the main strategy to detect early-stage disease. 13 In particular, the endoscopic examination of patients with a high clinical suspicion of gastric cancer, especially with a positive familial history, is recommended.…”
Section: Discussionmentioning
confidence: 99%